Efficacy of minute virus of mice (MVM) inactivation utilizing high temperature short time (HTST) pasteurization and suitability assessment of pasteurized, concentrated glucose feeds in Chinese hamster ovary (CHO) cell expression systems. Issue 7 (11th June 2021) - Gemmell, David K.; Mack, Aaron; Wegmann, Sabrina; Han, David; Tuccelli, Ronald; Johnson, Matthew; Miller, Corinne
Abstract: There is a growing need to provide effective adventitious agent mitigation for high risk upstream cell culture raw materials used for the production of biologics. It is also highly important in the growing fields of cell and gene therapies. Glucose is a critical raw material necessary for effective cell growth and productivity; however, glucose is the highest risk animal‐origin‐free raw material for viral contamination, and often the highest risk raw material in the upstream process as more companies move to chemically defined media. This study examines the efficacy of utilizing High Temperature Short Time (HTST) pasteurization for inactivation of physiochemically resistant, worst‐case parvovirus using a bench‐scale HTST system. We demonstrated approximately six log inactivation of Minute Virus of Mice (MVM) in concentrated glucose feeds without impacting the subsequent performance of the glucose in a Chinese Hamster Ovary (CHO) expression system.